Immigrants : Your Country Needs Them - Legrain, Philippe (Book collections on Project MUSE., 2007)
"Immigration divides our globalizing world like no other issue. We are swamped by illegal immigrants and infiltrated by terrorists, our jobs stolen, our welfare system abused, our way of life destroyed- or so we are told. At a time when National Guard units are deployed alongside vigilante Minutemen on the U.S.-Mexico border, where the death toll in the past decade now exceeds 9/11's, Philippe Legrain has written the first book about immigration that looks beyond the headlines. Why are ever-rising numbers of people from poor countries arriving in the United States, Europe, and Australia? Can we keep them out? Should we even be trying? Combining compelling firsthand reporting from around the world, incisive socioeconomic analysis, and a broad understanding of whats at stake politically and culturally, Immigrants is a passionate but lucid book. In our open world, more people will inevitably move across borders, Legrain says--and we should generally welcome them. They do the jobs we cant or wont do--and their diversity enriches us all. Left and Right, free marketeers and campaigners for global justice, enlightened patriots--all should rally behind the cause of freer migration, because They need Us and We need Them."--Jacket